Abnormal intrafusal muscle fibres in myotonic dystrophy: a study using serial sections. Issue 1 (January 1975) - Swash, M.; Fox, K. P.
Abstract : Studies of the extent and complexity of intrafusal muscle fibre splitting in myotonic dystrophy have been carried out in three spindles obtained at muscle biopsy, and in nine spindles found in the lumbrical muscle of a case that came to necropsy. It is suggested that splitting, due to mechanical stresses, leads to a regenerative response in the separated fragments.